0P24. T cells and anti-inflammatory interleukins in skin biopsies of Complex Regional Pain Syndrome (CRPS). Issue 8 (August 2015) - Schlereth, T.; Bolz, S.; Albrecht, N.; Birklein, F.
<x xml:space="preserve">Abstract</x> Introduction CRPS (Complex regional Pain Syndrome) is a neuropathic pain syndrome occurring after trauma. It is associated with increased posttraumatic inflammation. Patients show inflammatory signs like increased skin temperature, edema, hyperhidrosis, and hypertrichosis. In CRPS blood samples pro-inflammatory cytokines were increased and anti-inflammatory cytokines reduced. We found in skin biopsies an increase of pro-inflammatory cytokines (TNF-α, Il-6) and mast cells. The aim of this study was the quantification of T cells and the immunohistochemical staining of anti-inflammatory interleukins and of Interferon-γ (IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj1f28fqrk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ)</alternatives> in the skin of CRPS patients. Method Bilateral skin biopsies were taken from 17 patients with acute CRPS (duration <6 months) affecting the upper extremity. Skin samples (diameter 3 mm) were embedded in paraffin and immunohistochemistry was performed with antibodies directed against Il-10 (interleukin-10), Il-4, CD4 (marker of CD4+ T-helper cells), CD8 (marker of cytotoxic T-cells), CXCR3 (marker of activated Th1 helper cells), and interferon-γ (IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj1f28fwxx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γ)</alternatives>. Result Epidermal staining for Il-10, Il-4 and IFN-γ was evaluated qualitative. However, only weak staining could be observed which did not differ between affected and control side. The number of IHC stained cells was counted per field of view (magnification 200 times). Only few CD4+ T-helper cells (7.2 ± 2.3 (affected) vs. 8.9 ± 3.1; n.s.), CD8+ cytotoxic cells (3.3 ± 0.6 (aff) vs. 5.5 ± 2.3; n.s.) and CXCR3+ Th1-helper cells (4.0 ± 1.1 (aff) vs. 2.8 ± 0.6; n.s.) without side differences could be detected. The number of IFN-γ positive cells (17.3 ± 2.4 (aff) vs. 21.7 ± 3.7; n.s.) and Il-4 positive cells (0.5 ± 0.2 (aff) vs. 0.3 ± 0.1; n.s.) did not differ between affected and control side. The number of Il-10 positive cells was significantly higher on the affected side. However, overall cell number was very low and this effect was only significant for the deep dermis, not the superficial dermis (1.1 ± 0.3 vs. 0.4 ± 0.2; p < 0.05). Conclusion No signs of cellular inflammation could be found in CRPS skin; IFN-γ as a marker of Th1 activation was also unchanged. The anti-inflammatory cytokine Il-4 was not different from the control side and only a slight increase of the anti-inflammatory Il-10 was found in the deep dermis. Previous data suggest increase of Il-10 after trauma. Our results have to be compared to normal fracture healing, but one hypothesis for the development of CRPS could be a reduction of anti-inflammatory mediators.